Micromechanical sensing for real time monitoring of filamentous fungi growth - Maloney, Niall (Trinity College (Dublin, Ireland). School of Physics, 2013)
Since the early 1990s the use of cantilevers as biosensors has risen dramatically. Advances in semiconductor fabrication technologies has resulted in the reproducible production of high quality cantilever arrays. When operated in dynamic mode the cantilever is oscillated at its resonance frequency. Mass loading on the sensor produces a shift in resonance frequency, thus rendering the cantilever an uhra-sensitive ‘mass balance’. Despite this high sensitivity there has only been a limited number of incidences where cantilevers have been employed for the real time monitoring of microorganism growth. In this thesis the development of several devices designed for the measurement of cantilever resonance frequencies is outlined. As it is desired to use cantilevers for fast microorganism growth detection these devices have been designed accordingly.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin